2003
DOI: 10.1089/107632703762687645
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Transplanted Tissue-Engineered Oral Mucosa Equivalents in Severe Combined Immunodeficient Mice

Abstract: The aim of this study was to determine the optimal stage of development at which transplant human ex vivo-produced oral mucosa equivalents (EVPOMEs) in vivo. EVPOMEs were generated in a serum-free culture system, without the use of an irradiated xenogeneic feeder layer, by seeding human oral keratinocytes onto a human cadaveric dermal equivalent, AlloDerm. EVPOMEs were cultured for 4 days submerged and then for 7 or 14 days at an air-liquid interface to initiate stratification before transplantation into SCID … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 41 publications
4
41
0
2
Order By: Relevance
“…At the end of this study, histological findings of "EVPOME"s development showed the same epithelial architecture as the previous studies performed by Izumi et al (9,25). Also, the epithelial architecture of "EVPOME"s resembled that of normal oral mucosa.…”
Section: Discussionsupporting
confidence: 86%
“…At the end of this study, histological findings of "EVPOME"s development showed the same epithelial architecture as the previous studies performed by Izumi et al (9,25). Also, the epithelial architecture of "EVPOME"s resembled that of normal oral mucosa.…”
Section: Discussionsupporting
confidence: 86%
“…13 In addition ex vivo produced oral mucosal equivalents have been fabricated 25 and grafted into humans. 26 However, they have been separately implemented and the oral constructs have only been used for intraoral grafting procedures.…”
Section: Figmentioning
confidence: 99%
“…35 Other dermal substitutes for development of nonkeratinized oral mucosa constructs have been reported using collagen-based membranes. 36 The testing of these 3D constructs in vivo could initially be done by grafting the constructs into athymic (nude) rats to allow integration with the underlying striated muscular bed as previously done with mice 25 to evaluate vascular ingrowth. It has been shown in clinical trials that use of the Alloderm Ò as a dermal substitute without the presence of fibroblasts in keratinized oral mucosa repair is successful on transplantation.…”
Section: Figmentioning
confidence: 99%
“…Surgical procedures in mice were detailed in a previous article (Izumi et al 2003). Briefly, each batch of control and stressed EVPOMEs was grafted into 7-to 8-wk-old SCID mice (Charles River Laboratories, Wilmington, MA) for 1 wk.…”
Section: Mice Surgery For Evpomes Grafting and Postimplanted Evpome Hmentioning
confidence: 99%